The Japanese house : material culture in the modern home - Andrews, Susan (Routledge, 2010)
In the West the Japanese house has reached iconic status in its architecture, decoration and style. Is this neat, carefully constructed version of Japanese life in fact a myth? Inge Daniels goes behind the doors of real Japanese homes to find out how highly private domestic lives are lived in Japan. The book examines every aspect of the home and daily life-from decoration, display, furniture and the tatami mat, to eating, sleeping, gift-giving, recycling and worship. For students and researchers in anthropology and architecture, The Japanese House re-evaluates contemporary Japanese life through an ethnographic lens, examining key topics of consumption, domesticity and the family. Highly illustrated throughout, the book will appeal to all those who are interested in Japanese culture, and in how and why people live the way they do in modern Japan.